Evaluation of Serum microRNA Let-7c and Let-7d as Predictive Biomarkers for Metastatic Pancreatic Cancer - Atike Gökçen Demiray,; Aydın Demiray,; Arzu Yaren,; Burcu Taşköylü,; Gamze Gököz Doğu,; Serkan Değirmencioğlu,; Umut Çakıroğlu,; Nail Özhan,; Canan Karan,; Burçin Çakan Demirel,; Tolga Doğan,; Melek Özdemir, (Turkish Journal of Gastroenterology, 2022)
Background: First-line treatments for metastatic pancreatic cancer are chemotherapy regimens consisting of 5-fluorouracil or gemcitabine; however, there are no biomarkers to help determine which patients might benefit from which treatment regimens. We aimed to show that microRNAs let-7c and 7d can be used as independent predictive biomarkers for metastatic pancreatic cancer.Methods: A total of 55 patients who had first-line chemotherapy with FOLFIRINOX or gemcitabine+capecitabine were included. Patients were divided into groups based on let-7c and let-7d levels and chemotherapy treatment as let-7c-7d high FOLFIRINOX, let7c-7d high gemcitabine+capecitabine, let-7c-7d low FOLFIRINOX, and let-7c-7d low gemcitabine+capecitabine. Blood samples were taken from patients before chemotherapy for microRNA let-7c and 7d analysis. MicroRNA isolation was performed using a miRNeasy Serum/Plasma Kit and identified using spectrophotometric measurements. After isolation, microRNA was converted to cDNA using a microRNA cDNA Synthesis Kit with poly (A) polymerase tailing. The expression of microRNA was examined using quantitative real-time polymerase chain reaction.Results: The overall survival of patients who received FOLFIRINOX treatment with a high let-7c-7d level was statistically significantly longer than those who received gemcitabine+capecitabine with a high let-7c-7d level. In addition, patients with low let-7c expression receiving FOLFIRINOX progressed significantly 2.104 times earlier than patients with high let-7c expression receiving FOLFIRINOX.Conclusion: The serum MicroRNA let-7c level was found to be an independent predictive biomarker in the FOLFIRINOX treatment group.Cite this article as: Demiray AG, Demiray A, Yaren A, et al. Evaluation of serum microRNA let-7c and let-7d as predictive biomarkers for metastatic pancreatic cancer. Turk J Gastroenterol. 2022;33(8):696-703.